2004
DOI: 10.4067/s0716-078x2004000300014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic differentiation among Chilean populations of Bufo spinulosus (Anura: Bufonidae)

Abstract: Bufo spinulosus has a wide and fragmented distribution range in Chile (18° to 33° S) along altitudinal and latitudinal gradients. Genetic variation was estimated using RAPD (Random Amplified Polymorphic DNA) markers in 10 populations from northern and central Chile. Morphometric and genetic information was analyzed as a function of geographical origin. The correlation between genetic and morphometric differentiation was analyzed by the Mantel test. An increase in body size as a function of latitude was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
5
12
0
5
Order By: Relevance
“…According to another hypothesis of (Nevo 1972), there is a clinal variation with increasing body size from north to south in B. viridis. Similar findings have also been reported for other bufonids such as B. spinulosus from Chile (Mendez et al 2004) and B. bufo from France (Hemelaar 1988), and for spotted marsh frogs, Limnodynastes tasmaniensis and L. peronii, from Australia (Schauble 2004). But our results suggest that there is a trend of increasing body size from humid (lowland) areas to desert (highland) areas (Table 1) instead of north to south.…”
Section: Discussionsupporting
confidence: 87%
“…According to another hypothesis of (Nevo 1972), there is a clinal variation with increasing body size from north to south in B. viridis. Similar findings have also been reported for other bufonids such as B. spinulosus from Chile (Mendez et al 2004) and B. bufo from France (Hemelaar 1988), and for spotted marsh frogs, Limnodynastes tasmaniensis and L. peronii, from Australia (Schauble 2004). But our results suggest that there is a trend of increasing body size from humid (lowland) areas to desert (highland) areas (Table 1) instead of north to south.…”
Section: Discussionsupporting
confidence: 87%
“…Molecular phylogeny of these different populations will be able to help us in separating the population level variations from the species level variations and help us in studying the monophyly of H. malabarica. Méndez et al (2004) also suggested similar strategy to reveal the presence of recent speciation in Bufo spinulosus, who conducted similar study on this species. Additionally, ecological studies on these populations using niche modeling method (Raxworthy et al 2007) will also be interesting and may probably help in resolving the phylogeny of H. malabarica.…”
Section: Discussionmentioning
confidence: 85%
“…Así, estudios en sistemática basados en la morfología de los organismos requieren técnicas de descripción y comparación de la estructura de las formas (Rohlf 1990, Bernaltaxonómicas y filogenéticas entre ellos, por ejemplo, descartando o aceptando diferencias entre grupos de individuos que ocupaban un nivel taxonómico incierto (Barrio 1965, Cei 1980, Heyer et al 1990, Arikan et al 1998, Maneyro & Arrieta 2000, Lobo 2001Lobo & Abdala 2001, Oliver & Lobo 2002, Méndez et al 2004, Arroyo et al 2005, Fabrezi 2006). Debido a la limitada capacidad de dispersión y filopatría en anfibios (Seppä & Laurila 1999;Lampert et al 2003), es frecuente que poblaciones separadas geográficamente presenten diferencias intraespecíficas en sus estructuras morfológicas, particularmente en el tamaño corporal, generadas por una acumulación de diferencias genéticas y morfológicas debido a este aislamiento geográfico , Laugen et al 2002, Schäuble 2004).…”
Section: Palabras Claveunclassified